2002
DOI: 10.1007/s005950200162
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration of Small Bowel Herniation Through a Defect of the Broad Ligament of the Uterus: Report of a Case

Abstract: Intestinal herniation through a defect in the broad ligament of the uterus is uncommon among internal herniations. We herein report a 59-year-old woman with intestinal obstruction, who had no previous history of surgical treatment except for an appendectomy. The laparotomy revealed an incarceration of the small bowel herniation through the defect of the right broad ligament. This possibility should therefore be considered in the differential diagnosis for female patients presenting with an intestinal obstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…10 A defect of the broad ligament is often present in a unilateral portion, and several etiological factors for such defects have been suggested, including trauma during pregnancy or delivery, surgical injury, pelvic inflammatory disease, and congenital anomalies. 4,[10][11][12][13][14] In the current case, the etiology of the disease could be multifactorial since our patient had a history of pregnancy, delivery, and abdominal surgery. Although it is difficult to determine the precise contributions of each factor, we believe that the patient's previous hysterectomy likely played a major role in the formation of the defect in the residual broad ligament.…”
Section: Discussionmentioning
confidence: 99%
“…10 A defect of the broad ligament is often present in a unilateral portion, and several etiological factors for such defects have been suggested, including trauma during pregnancy or delivery, surgical injury, pelvic inflammatory disease, and congenital anomalies. 4,[10][11][12][13][14] In the current case, the etiology of the disease could be multifactorial since our patient had a history of pregnancy, delivery, and abdominal surgery. Although it is difficult to determine the precise contributions of each factor, we believe that the patient's previous hysterectomy likely played a major role in the formation of the defect in the residual broad ligament.…”
Section: Discussionmentioning
confidence: 99%
“…reported the first case of laparoscopic repair of a hernia through a broad ligament in 2003 , and since then, the procedure has become the mainstay of treatment for uncomplicated cases. The defect in the broad ligament is repaired primarily using clips or sutures, or the broad ligament can be completely divided . In cases in which the patient has SBO and suspected internal hernia, but there is no evidence of necrosis or perforation of the hernial contents, we believe the first choice should be a diagnostic laparoscopy because of ease, minimal aesthesia and minimal invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Even though all of the studies are of low LE, the potential role of laparoscopy in the diagnosis seems to be demonstrated in them and would, at times, prevent unnecessary laparotomies [298][299][300][301][302][303][304][305][306][307][308][309][310][311][312][313][314][315][316][317].…”
Section: Incarcerated/strangulated Herniasmentioning
confidence: 99%